(untitled) (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Acute tonsillitis is a common reason for seeking medical evaluation in primary health care (PHC) in pediatric age. Although the majority of cases have a viral etiology, 35% are caused by bacteria and, consequently, require antibiotic treatment. The use of rapid antigenic diagnostic tests (RADTs) aids in both diagnosis and the identification of the most common causal agent. Objectives: (1) Assessment of the importance of using RADT in the diagnostic and therapeutic guidance of patients; and (2) estimation of the costs of a large-scale use of RADT and whether this use could result in a reduction in the costs of treating these patients. Methods: An observational, retrospective, and descriptive study was conducted between January 2021 and May 2024 at the ULS of Entre Douro e Vouga units. The sample is made up of pediatric patients diagnosed with acute tonsillitis. The statistical analysis was carried out using SPSS. Results: Eight hundred and thirty-two episodes of acute tonsillitis were analyzed, most of them in FHU-B. In these, RADT was used in 66.1% of cases. The use of RADT contributed to significantly lower antibiotic prescriptions, as well as a reduced need for reevaluation consultations. The age of the clinician, the clinician’s gender, and the type of PHC unit were important factors in both the use of the test and antibiotic prescription. Economically, the implementation of RADT does not increase the cost of the medical procedure and results in a significant reduction in the total cost of the treatment. Conclusion: The use of RADT proves to be a crucial tool in diagnosing and identifying the etiological agent in patients with acute tonsillitis, thereby improving therapeutic guidance and reducing the costs associated with their treatment.